Comprehensive Budget and Sales Analysis for Improved Financial Performance - Shivani Katkar; Manasi Korake; Rutuja Gaikwad; Shital Ghodake; Swarupa Rathod; V.D. Jadhav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper presents a Comprehensive Budget and Sales Analysis for Improved Financial Performance explores the critical relationship between budgeting, sales forecasting, and financial outcomes. Budgeting, traditionally a cornerstone of financial management, ensures efficient resource allocation, cost control, and alignment with organizational objectives. However, static budgeting methods often struggle to keep pace with today’s dynamic business environments. By leveraging Python’s extensive suite of libraries, such as Pandas, NumPy, Matplotlib, and Seaborn, this project automates data cleaning, processing, and visualization to provide deeper insights into budget utilization and sales trends. The analysis identifies revenue streams, cost-saving opportunities, and areas requiring strategic investment. Advanced predictive models using machine learning algorithms such as Linear Regression, ARIMA, and Decision Trees are incorporated to forecast future sales trends, enabling proactive budget adjustments and enhanced financial planning. This system emphasizes the importance of aligning budget allocation with market performance, ensuring resources are optimized to achieve business objectives.